Effectiveness of an Intervention Oriented Program on the Prognosis of Osteopenia among Women at Private Clinics in Baghdad City - hasan, aqeel; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2016)
Objective: To determine the effectiveness of an Intervention Oriented program on the prognosis of Osteopenia among Women at Private clinics in Baghdad City. Methodology: A longitudinal design. A purposive ’’non probability’’ sample of (25) Women who have bone mineral density (BMD) T- test between (-1 to -2.5). The data are collected through the utilization of a constructed questionnaire and by means of interview with each client who is involved in the study. Each interview takes approximately (20) minutes. Results: The study showed that there is a good improvement in bone density accord after application of an intervention oriented program on the study sample (women). This improvement began in the first period, and became clear in the second period; in the third period the improvement became excellent in the each foot right and left. Recommendation: The study recommends that early detection of osteopenia in women is very important to prevent or at least delay the onset of symptoms, and the implementation of all parts of an intervention oriented program sports, nutrition, and pharmacology have positive benefits on bone mineral density, as recommended by the study it’s very important to increase the health awareness about osteopenia throughout various media channels such as radio, television, newspapers and magazines. And it’s very important application of screening program for effective strategies of the early detection of obesity at each main primary health care center in health sector nationwide.